2016
DOI: 10.1292/jvms.15-0277
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect for proliferation of oral bacteria in dogs by tooth brushing and application of toothpaste

Abstract: To investigate inhibitory effect for oral bacterial proliferation, we divided 12 dogs into 3 groups; scaling alone (C; control group), brushing (B) and application of toothpaste (P). Before scaling (Pre) and at 0 to 8 weeks after scaling (0–8 w), we collected oral bacteria from the dental surface every week and counted them using a bacterial counter. The results demonstrated a significant reduction in the number of oral bacteria for group B relative to Pre and group C, as well as for group P relative to group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…, Watanabe et al . ). As a result, other methods of plaque control such as dental hygiene chews or specifically formulated dental foods have been developed, with published evidence that they can reduce plaque accumulation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Watanabe et al . ). As a result, other methods of plaque control such as dental hygiene chews or specifically formulated dental foods have been developed, with published evidence that they can reduce plaque accumulation.…”
Section: Introductionmentioning
confidence: 97%
“…Minimising plaque accumulation is the key means of preventing gingivitis and PD, and various methods of control have been marketed for the pet-owning public (Roudebush et al 2005). While tooth brushing has been long recognised as the gold standard control measure, there are well-recognised challenges associated with this method: notably, owner and patient compliance (Roudebush et al 2005, Harvey et al 2015, Watanabe et al 2016. As a result, other methods of plaque control such as dental hygiene chews or specifically formulated dental foods have been developed, with published evidence that they can reduce plaque accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Dental brush and rubber or silicone fingerstall were equally efficient in removing plaque, concluding that choice of instrument should be guided by the ease of handling by the dog owners. Watanabe et al, (2016) found that brushing significantly reduced the number of oral bacteria either alone or with use and toothpaste, in relation to the non-brushed group. Dentifrice was effective in the bacteria inhibition, but not exceeding the brushing, being its application advantageous and easy for the dogs' oral care (Watanabe et al, 2016) A good brushing technique may be associated with the use of dentifrice and oral antiseptic agents aiming to expand the oral hygiene benefits.…”
Section: Periodontal Disease and Oral Carementioning
confidence: 86%
“…Watanabe et al, (2016) found that brushing significantly reduced the number of oral bacteria either alone or with use and toothpaste, in relation to the non-brushed group. Dentifrice was effective in the bacteria inhibition, but not exceeding the brushing, being its application advantageous and easy for the dogs' oral care (Watanabe et al, 2016) A good brushing technique may be associated with the use of dentifrice and oral antiseptic agents aiming to expand the oral hygiene benefits. However, the fluoridated toothpaste commonly used by people is not suitable for dogs, because it can cause toxicity, since the animals ingest product during brushing, instead of spitting it (Gorrel et al, 2007).…”
Section: Periodontal Disease and Oral Carementioning
confidence: 86%
“…Brushing has previously been determined to be an effective means of reducing plaque biofilm in vivo. 59,60 Sixty seconds was spent using the microbrush to disrupt the biofilm on the hydroxyapatite coated surface and the resulting solution was assessed using serial dilutions to determine relative CFU/mL between trials. The dilutions were spiral plated on Brucella agar and duplicate plates were incubated at 5% CO 2 for counts of Actinomyces canis and Neisseria canis and anaerobically for counts of Porphyromonas gulae (Tables 2 and 3).…”
Section: Methodsmentioning
confidence: 99%